Allah dalam Bible, boleh atau tidak? Satu sudut Al-Quran Anas Zubedy, terjemahan oleh Bhuvanes Krishnasamy - Anas Zubedy
This book is a call for us to make peace and reconcile. Today, religion has become a divider that divides our society. Religion as the cause of separation has a wide and deep influence. If there is no solution as soon as possible, it can have tragic consequences. The book puts forward two propositions for resolving the issue of the use of the term ?Allah? to refer to God in the Bible: a view of the Qur?an?s angle in this regard; and the call for Muslims to emulate the Prophet Muhammad and Christians to emulate Jesus in their actions, in line with the true spirit of their faith